Single and Double Mutations in Tomato Ripening Transcription Factors Have Distinct Effects on Fruit Development and Quality Traits - Adaskaveg, Jaclyn A.; Silva, Christian J.; Huang, Peng; Blanco-Ulate, Barbara (Frontiers in Plant Science, 2021)
Spontaneous mutations associated with the tomato transcription factors COLORLESS NON-RIPENING (SPL-CNR), NON-RIPENING (NAC-NOR), and RIPENING-INHIBITOR (MADS-RIN) result in fruit that do not undergo the normal hallmarks of ripening but are phenotypically distinguishable. Here, we expanded knowledge of the physiological, molecular, and genetic impacts of the ripening mutations on fruit development beyond ripening. We demonstrated through phenotypic and transcriptome analyses that Cnr fruit exhibit a broad range of developmental defects before the onset of fruit ripening, but fruit still undergo some ripening changes similar to wild type. Thus, Cnr should be considered as a fruit developmental mutant and not just a ripening mutant. Additionally, we showed that some ripening processes occur during senescence in the nor and rin mutant fruit, indicating that while some ripening processes are inhibited in these mutants, others are merely delayed. Through gene expression analysis and direct measurement of hormones, we found that Cnr, nor, and rin have alterations in the metabolism and signaling of plant hormones. Cnr mutants produce more than basal levels of ethylene while nor and rin accumulate high concentrations of abscisic acid. To determine genetic interactions between the mutations, we created for the first time homozygous double mutants. Phenotypic analyses of the double ripening mutants revealed that Cnr has a strong influence on fruit traits and that combining nor and rin leads to an intermediate ripening mutant phenotype. However, we found that the genetic interactions between the mutations are more complex than anticipated as the Cnr/nor double mutant fruit has a Cnr phenotype but displayed inhibition of ripening-related gene expression just like nor fruit. Our reevaluation of the Cnr, nor, and rin mutants provides new insights into the utilization of the mutants for studying fruit development and their implications in breeding for tomato fruit quality.